Comparison of common wheat and spelt by total lipids and fatty acid levels - Relina, L.; Suprun, O.; Bohuslavskyi, R.; Vecherska, L.; Leonov, O.; Antsyferova, O.; Golik, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2021)
Nowadays the interest of breeders, producers and consumers is going back to ancient wheat species, such as Triticum spelta, which are often considered as more valuable for healthy nutrition. In this light, we compared spelt cultivars and breeding lines with commercial common wheat cultivars by total lipid content, fatty acid levels and unsaturated/saturated ratio in grain. Lipids were extracted by Soxhlet procedure. Fatty acid composition was determined by gas chromatography. On average, the total lipid content was higher in the spelt cultivars than in the breeding spelt lines (3.04±0.24 % vs. 2.23±0.69 %, p < 0.05). There was a significant difference between the average content of total lipids in the spelt cultivars, but not the breeding spelt lines, and the common wheat cultivars (3.04±0.24 % vs. 2.44±0.57 %, p < 0.05). Six major fatty acids were found in hexaploid wheat species, with linoleic acid being the most abundant. They are ranked in order of decreasing levels as follows: linoleic > oleic >palmitic > linolenic > stearic > palmitoleic. We also detected trace amounts of 3 minor fatty acids: eicosanoic (arachidic), eicosenoic and behenic acids. Common wheat is not inferior to spelt in terms of unsaturated fatty acid levels, because the ratios of unsaturated acids to saturated ones in grain of T. spelta accessions were similar to those in commercial common wheat cultivars. The oleic acid content was higher in spelt accessions; though the linoleic acid content was higher in T. aestivum cultivars. Spring common wheat cultivar Heroinia had the most beneficial unsaturated/saturated ratio of 4.5. We detected no differences in unsaturated acid amounts between spring and winter hexaploid wheats. We observed no patterns in variability of fatty acid contents across the accessions under investigation, because the same accession can be characterized by a wide variability in one fatty acid and by a narrow range for another, and, at the same time, the same fatty acid can be very variable within one accession and little variable in another. There were no significant differences in the total lipid content and fatty acid levels between the study years for the same accession.